A Comprehensive Survey of Rock Art in Upper Tibet Volume I Eastern Byang thang - Bellezza, John Vincent (2023)
Focusing on the eastern part of the region, this is the first in a series of five volumes that comprehensively document rock art in Upper Tibet. It examines a panoply of graphic evidence found on stone surfaces, supplying an unprecedented view of the long-term development of culture and religion on a large swathe of the Tibetan Plateau. The pictographs (rock paintings) and petroglyphs (rock carvings), host sites, and descriptions and analyses presented are the direct result of intensive fieldwork conducted by the author in Upper Tibet between 1995 and 2016. Information on rock art production techniques, subject identification, thematic class, mode of presentation, physical condition, estimated age, and relative location are supplied for each piece of rock art. In addition to the datasets, the book offers rock art site descriptions and assesses the cultural, religious and artistic development of these locations.